Talking Local: Florida Consumers’ Reasons for Purchasing Local Food - Caroline G. Roper; Joy N. Rumble (EDIS, 2017)
This is a minor revision of an EDIS publication focusing on understanding Florida consumers’ reasons for purchasing local food. It is the third in the Talking Local series, a six-part EDIS publication series about Florida consumers and their perceptions of local food. This series focuses on ways Extension agents can assist Florida farmers and ranchers in the labeling, sale, and promotion of locally produced products. This series provides information about Florida consumers’ perceptions of local food to Extension faculty who are interested in local food programming or who work with local food clientele. This 4-page fact sheet was written by Caroline G. Roper and Joy N. Rumble, and published by the Department of Agricultural Education and Communication, November 2017.